Fenomena FOMO (Fear of Missing Out) di Era Digital: Studi tentang Dampaknya pada Gen Z - Hidayati, Yusranida; Nasution, Muhammad Irwan Padli (Innovative: Journal Of Social Science Research, 2025)
This The phenomenon of Fear of Missing Out (FOMO) has become increasingly prevalent in the digital era, particularly among Gen Z, who are highly dependent on information technology and social media. This study aims to analyze the impact of FOMO on the social, psychological, and academic aspects of Gen Z's life. The research employs a qualitative approach through a literature review and surveys conducted among Gen Z respondents. The findings indicate that FOMO significantly affects Gen Z's mental health, productivity, and social interactions. This study recommends strategies to mitigate FOMO through digital literacy, time management, and increased awareness of the importance of life balance.